لاصاص" بين تأطير السكان المحليين وإفشال الثورة التّحريرية (1954-1962" - حسين, عبد الهادي (جامعة الوادي University of Eloued, 2017)
تندرج هذه المساهمة في الدِّراسات الخاصَّة بتاريخ الإدارة المحلية الاستعمارية الفرنسية في الجزائر، إذ حاولَتْ تسليط الضَّوء على أحد جوانبها المتمثل في الفرق الإدارية المختصة "لاصاص" في الفترة ما بين نهاية سبتمبر 1955 وجوان 1962. وبينت الدِّراسة بأن هذه الفرق أريد لها أن تكون أداة للحرب الحقيقية، وجهازًا لتجاوز التّحديات التي خلقتها الثورة، وآلية لعزل الشعب ومنعه من التفافه حول ثورته. وناقشت جملة من القضايا المرتبطةِ بالخلفيات و الجذور التاريخية لنشأة الفرق الإدارية المختصة، وأبرزت أهم الأخطار التي واكبت فترة نشاطها بالإضافة إلى علاقتها بمصالح الاستعلامات وموقعها من خطط الحرب البسيكولوجية التي مارستها جميع المصالح الأمنية الفرنسية. وأوضحت ارتباط تاريخ الفرق الإدارية المختصة بنشاط "الحركي" و"المخازنية" وباقي المجموعات الموالية للاستعمار وزُمَرِه المختلفة. وأيضا علاقاتها بالمعاقل المناوئة للثورة التي خَلَقت لجيش التحرير الوطني صعوبات جمّة. This contribution has searched the specialized studies in the history of French colonial local government in Algeria. He sheds light on one of its sides which is specialized administrative sections within the period Ranging from late September 1955 to June 1962. The study has shown to have wanted to make these sections a tool of war and a real body for the challenges countered that created the revolution. And a mechanism to prevent the revival of the Algerian people and break the institutions of the revolution end weaken the structural map of the revolution and isolate the people and forbid him to embrace his revolution. And discussed a number of cases in connection with the thought back and the historical roots of the genesis of specialized administrative sections. The study addressed the real issues of specialized administrative sections and want to realize (assimilation) and building (the new Algeria). and showed significant danger that accompanied the period of its activity and in addition to its relationship with the intelligence services and its position in the psychological war plans has practiced all French security services and clarify the relationship history specialized administrative sections with HARKIS and EL MEGHAZNIS activity and the remaining groups are acting with colonialism and these acolytes. And its relationship with the groups against marquis during the revolution that creates several problems in the armed national liberation (A.L.N.)
Keywords: لإدارة المحلية الاستعمارية الفرنسية، الفرق الإدارية المختصة، المكاتب العربية، الجزائر الفرنسية، التأطير الثوري، الحركي، الحركات المناوئة للثورة